Headmaster's Strategies to Improve the Quality of Education: A Case Study at Kindergarten ABA Warungboto - Adwiah, Amalia Rabiatul; Munastiwi, Erni (JOYCED: Journal of Early Childhood Education, 2023)
Improving the quality of schools is basically a strategy to improve the quality of education by giving authority and responsibility to school leaders to make decisions. The principal as the leader of an educational institution and of course being the key holder of the school's success needs to have various methods and efforts made to achieve the stated goals. desired. The aim of this research is to determine the school principal's efforts to improve the quality of education at the ABA Warungboto Kindergarten. The approach used in the research is a descriptive qualitative type approach. The subjects in this research were the principal and two homeroom teachers who were the main sources for obtaining research data. Three methods were used to collect research materials, namely interviews, observation and documentation. The data analysis techniques used in this research are data reduction, data display, and drawing conclusions. The results of the research show that there are various efforts made to improve the quality of education, including a) Division of tasks and responsibilities b) Improving the quality of teachers c) Increasing student achievement d) Improving infrastructure. Various efforts made by school principals can ensure quality that can help improve schools in the future.